(untitled) (Journal of Statistics on Health Decision, 2021)
Aims: Analise agreement of WHODAS 2.0-12 items, Portuguese version, applied by telephone or digital media for people aged 50 or more years old. Method: Face-to-face, telephone and digital media versions were conducted in 31 participants, with an interval of three days between applications. Internal consistency was assessed with Cronbach’s Alpha and an agreement was analyzed with Intraclass Correlation Coefficient and Bland-Altman plots. Results: The telephonic and digital media versions of the WHODAS 2.0–PT12 has shown good internal consistency. Agreement between face-to-face vs telephone application was ICC=0.99 (CI95%=[0.98-1.00]), and between face-to-face vs digital media was ICC=0.98 (CI95%=[0.96-0.99]). The Bland-Altman plots revealed no systematic bias. Application by telephone or by digital media discriminate different levels of overall functioning, and between institutionalized and non-institutionalized participants. Conclusions: WHODAS 2.0 - PT12 applied by telephone or digital media to people 50 years of age or older showed excellent agreement with face-to-face administration.